Dynamics of power: an architectural reading of the concentration of power (Ullastret, 4th-3rd Century BC) / Dinámica de poder: una lectura sobre la concentración de poder a partir de la arquitectura (Ullastret, siglos IV-III a. C.) - David Cebrián-Martínez (Panta rei, 2018)
This paper discuss the role of domestic architecture in the construction of narratives of power and its importance as a key feature to determine and analyse both the economic system and the social change in the 4th-3rd century BC. On the one hand, scrutiny of domestic architecture is a fruitful way by which to draw out a deeper insight with respect to social organisation, as well as being an indicator of ideology. On the other hand, social change is frequently reflected in the household in the same way as it is in settlement structure. After taking into account the empirical analysis, this paper contributes by determining that power can be concentrated for a number of reasons. -- Este artículo analiza el papel de la arquitectura doméstica en la construcción de narrativas de poder y su importancia como elemento clave para profundizar en el estudio y conocimiento tanto del sistema económico como del cambio social en los siglos IV-III aC. La investigación y posterior análisis de la arquitectura doméstica conduce a un conocimiento más profundo de la organización social además de aportar claves sobre la ideología imperante. Por otra parte, el cambio social se refleja a menudo en el hogar de la misma manera que en el patrón de asentamiento. Después de llevar a cabo el análisis empírico, la contribución de este ensayo se fundamenta en la tesis de que el poder puede ser concentrado.